An integrative genomics approach for identifying novel functional consequences of PBRM1 truncated mutations in clear cell renal cell carcinoma (ccRCC). (August 2016) - Wang, Yuanyuan; Guo, Xingyi; Bray, Michael; Ding, Zhiyong; Zhao, Zhongming
Abstract Background Clear cell renal cell carcinoma (ccRCC) is the most common type of kidney cancer. Recent large-scale next-generation sequencing analyses reveal thatPBRM1 is the second most frequently mutated gene harboring many truncated mutations and has a suspected tumor suppressor role in ccRCC. However, the biological consequences ofPBRM1 somatic mutations (e.g., truncated mutations) that drive tumor progression in ccRCC remain unclear. Methods In this study, we proposed an integrative genomics approach to explore the functional consequences ofPBRM1 truncated mutations in ccRCC by incorporating somatic mutations, mRNA expression, DNA methylation, and microRNA (miRNA) expression profiles from The Cancer Genome Atlas (TCGA). We performed a systematic analysis to detect the differential molecular features in a total of 11 ccRCC samples harboringPBRM1 truncated mutations from the 33 "pan-negative" ccRCC samples. We excluded the samples that had any of the five high-confidence driver genes (VHL, BAP1, SETD2, PTEN andKDM5C ) reported in ccRCC to avoid their possible influence in our results. Results We identified 613 differentially expressed genes (128 up-regulated and 485 down-regulated genes using cutoff |log2 FC| < 1 andp < 0.05) inPBRM1 mutated group versus "pan-negative" group. The gene function enrichment analysis revealed that down-regulated genes were significantly enriched in extracellular matrix organization (adjustedp = 2.05 × 10−7 ), cell adhesion (adjustedp = 2.85 × 10−7 ), and ion transport (adjustedp = 9.97 × 10−6 ). Surprisingly, 26 transcriptional factors (TFs) genes includingHOXB9, PAX6 andFOXC1 were found to be significantly differentially expressed (23 over expressed TFs and three lower expressed TFs) inPBRM1 mutated group compared with "pan-negative" group. In addition, we identified 1405 differentially methylated CpG sites (targeting 1308 genes, |log2 FC| < 1, p < 0.01) and 185 significantly altered microRNAs (|log2 FC| < 1, p < 0.05) associated with truncatedPBRM1 mutations. Our integrative analysis suggested that methylation and miRNA alterations were likely the downstream events associated withPBRM1 truncation mutations. Conclusions In summary, this study provided some important insights into the understanding of tumorigenesis driven byPBRM1 truncated mutations in ccRCC. The approach may be applied to many driver genes in various cancers.